(untitled) (Bangladesh Journal of Medical Science, 2015)
Lateral Cephalometry (LCM) has been a mandatory diagnostic tool in orthodontics since a very long time. Nowadays with the advent of 3D imaging, the use of this two dimensional radiographic technique is questioned for its competence. However, there are few aspects which are overlooked and should be heeded before obsolete the technique completely from the field of orthodontics. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.313-315